Rancang Bangun Miniatur Crane Berbasis Motor 220v AC - Reza Al Ajani; Sonhaji Sonhaji; Upik Widyaningsih (Pusat Riset dan Inovasi Nasional, 2024)
A crane is a tool used to make it easier and easier to move and lift goods. This research aims to find a solution when the Joy Stick experiences sudden troubleshooting, how to overcome it, and prevent accidents while working. The creation of this tool is a miniature ship crane using a 220V Ac motor where the fan belt is the connecting part of the movement and can be controlled via a Joy stick. The design of this AC motor control system entirely uses the ESP32 microcontroller as the brain to be able to carry out slewing, luffing and hoisting movements. Researchers used research and development research methods to create and develop this crane prototype with the aim of producing and developing a crane prototype that is effective, efficient and easier to maintain. The test results of this prototype can carry out slewing movements to the left and right with a limit of 800, luffing movements upwards with a limit of 800 and hoisting.